A study to determine factors that contribute to re admission to chainama hills hospital. - Akalala Miriam (Lusaka: The University of Zambia, 1992)
Study was aimed at determining factors that contribute to patient readmission to chainam hills hospital; in order to identify risk groups.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: mental health services --chainama hills hospital --lusaka.; psychiatric hospitals --readmission --lusaka.; people with mental disabilities --institutional care --chainama hills hospital --lusaka.